Analisis Sebaran Air Limbah Industri Rumah Pemotongan Ayam Terhadap Kualitas Air Sungai Desa Kalitirto, Kecamatan Berbah, Kabupaten Sleman - Oddy Satria Bhaskara; Paramita Dwi Sukmawati*; Angge Dhevi Warisaura (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
The quality of the waters is influenced by the activities of living things around it, one of which is the activity of small industries that have not treated their wastewater optimally due to a lack of capital. One of the small industries that we often encounter and has the potential to contaminate is the chicken slaughterhouse industry (RPA), because RPA waste water contains high organic matter. This study used a case study approach to analyze the distribution of RPA wastewater on river water quality in Kalitirto Village, Berbah District, Sleman Regency. Data collection was carried out by taking samples of RPA wastewater, RPA groundwater, and river water. Tests were carried out in situ (pH) and in the laboratory (BOD, COD, TSS, total oil and fat). The measurement results of RPA liquid waste exceed the quality standard. The quality of river water before and after RPA is different. The result of the correlation coefficient is -0.829, meaning that the further away the RPA waste is in river water, the smaller the pollution index value. The probability result is 0.085, meaning that the relationship between the presence of liquid waste and the pollution index is not significant. The distribution of RPA waste does not occur in river water but enters the groundwater.